Expression of delta-like 4 (Drosophila) and vascular endothelial growth factor A in colon cancer and association with tumour angiogenesis. (August 2015) - Zheng, Yongbin; Hao, Zhinan; Ding, Yu; Wang, Qiushuang; Li, Shengbo; Xiao, Gaochun; Luo, Haiping; Shi, Qiang; Tong, Shilun
Objective: Angiogenesis depends on interaction between a variety of promoting and inhibiting factors, and is known to involve vascular endothelial growth factor (VEGF) A and the Notch signaling pathway. The present study investigated the expression of Notch ligand delta-like ( DLL ) 4 (Drosophila), and VEGFA in colon cancer and colorectal adenoma tissue, and the association with tumour angiogenesis. Methods: Protein level DLL4, VEGFA and CD34 molecule ( CD34 ) expression was detected immunohistochemically in tissue sections from patients with colon cancer and colorectal adenoma. Results: Out of 80 cases (35 with colon cancer, 45 with colorectal adenoma) DLL4 and VEGFA expression was closely related to tumour diameter, clinical stage, histological grade and lymph node metastasis. DLL4 expression was significantly higher in colon cancer tissue than colorectal adenoma tissue. Conclusion: High levels of DLL4 expression were closely related to metastasis and prognosis in patients with colon cancer. The results of the present study support the conclusion that prognosis of colon cancer is significantly correlated with angiogenesis.